2017
DOI: 10.1002/term.2444
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy for stress urinary incontinence: Present‐day frontiers

Abstract: Stress urinary incontinence (SUI) significantly diminishes the quality of patients' lives. Currently available surgical and nonsurgical therapies remain far from ideal. At present, advances in cellular technologies have stirred growing interest in the use of autologous cell treatments aimed to regain urinary control. The objective was to conduct a review of the literature and analyse preclinical and clinical studies dedicated to various cell therapies for SUI, assessing their effectiveness, safety, and future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…There are over 30 papers describing experiments in which functional assessment was performed after transplantation of cells into the experimentally injured urethra in small animal models. Interestingly, regardless of cell type, dose and other differences between protocols, all authors reported functional improvement after cell therapy in comparison to the control groups . These results encouraged clinical trials.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…There are over 30 papers describing experiments in which functional assessment was performed after transplantation of cells into the experimentally injured urethra in small animal models. Interestingly, regardless of cell type, dose and other differences between protocols, all authors reported functional improvement after cell therapy in comparison to the control groups . These results encouraged clinical trials.…”
Section: Introductionmentioning
confidence: 84%
“…Interestingly, regardless of cell type, dose and other differences between protocols, all authors reported functional improvement after cell therapy in comparison to the control groups. 1 These results encouraged clinical trials. Since 2007 more than 15 papers presenting results of cell therapy in SUI patients have been published.…”
mentioning
confidence: 98%
“…Stem cells have been used for more than 40 years for the treatment of hematologic diseases. Nevertheless, their multitherapeutic potential was reported only in 1999 when the cover of Science magazine announced, “Breakthrough of the year: stem cells show their therapeutic potential.” In recent years, the use of autologous stem cells aiming to halt disease progression and reverse underlying physiopathology of SUI has emerged as a promising approach to restore the anatomy and functionality of urinary sphincter and repair the neuropraxia …”
Section: Methodsmentioning
confidence: 99%
“…24 In recent years, the use of autologous stem cells aiming to halt disease progression and reverse underlying physiopathology of SUI has emerged as a promising approach to restore the anatomy and functionality of urinary sphincter and repair the neuropraxia. 25 2.7 | Bone marrow, amniotic fluid, and human cord blood-derived mesenchymal stem cells for SUI By definition, mesenchymal stem cells (MSCs) are multipotent stromal cells that can differentiate into a variety of cells, such as chondrocytes, myocytes, and adipocytes. MSCs can be isolated from all tissues derived from mesoderms, such as bone marrow, amniotic fluid, blood, adipose, cartilage, and skeletal muscle tissue.…”
Section: Stem Cells-based Therapy For Suimentioning
confidence: 99%
“…We read with great interest the article by Vinarov et al (), in a recent issue of the journal. We believe this is the first review article on cell therapy for stress urinary incontinence (SUI), and it is very informative for researchers and clinicians in that area.…”
mentioning
confidence: 99%